End of life care for people with dementia: an intervention to promote collaborative working between care home staff and healthcare practitioners. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Nicholson, Caroline; Goodman, Claire; Mathie, Elspeth; Amador, Sarah; Baron, Natasha; Machen, Ina
Abstract : Background: In England most care homes have no on-site clinician and rely on primary healthcare for end-of-life (EOL) support. The Evidem EOL study focused on end-of-life care for elders with dementia in care homes. Phase 1 found high levels of uncertainty among care home and primary healthcare staff around anticipating and supporting residents dying with or from dementia. This paper presents the piloting of a modified appreciative inquiry (AI) approach within Evidem EOL Phase 2 to facilitate end-of-life care for people with dementia in care homes. Methods: A modified AI approach (a strength-based change management tool) was implemented in three purposively sampled care homes over 6 months (January–July 2011). A self-selected team comprising care home staff, a general practitioner and a district nurse from each care home participated in the modified AI intervention: (3 one-hour AI meetings and on-going researcher support.) Through this intervention the teams developed and implemented context specific, participant driven strategies to support EOL care for people with dementia. Results: While evaluation is on-going, preliminary findings from thematic analysis of interviews with participants and collected data on use of emergency/acute services reveal: (1) High acceptance of the intervention, creating rapid engagement between participants who did not have a history of working together (2) Greater understanding and appreciation of respective roles and increased collaboration within the team (3) Improved EOL Care evidenced by increased advanced care planning; reduced number of emergency call outs and hospital admissions; increased staff confidence in talking to residents and family about end-of-life issues and wishes. Discussion: Long-term sustainability of the intervention remains to be tested. However preliminary findings suggest modified AI is an effective tool to promote integrated working between care home and health services and to improve EOL care for people with dementia in care homes.